PENGARUH KOMPETENSI, KOMITMEN DAN PENGALAMAN KERJA TERHADAP KINERJA DOSEN - Samuel . (Jurnal Bisnis dan Ekonomi, 2014)
Colleges require qualified competent human resources, one indicator can be seen from the performance of the lecturer. To the faculty performance needs to be improved in order to support the organization's overall performance as well as to improve / enhance the quality of university lecturers with competence development. This study aimed to analyze the influence of competence, commitment and work experience on the performance of the Semarang Merchant Marine Polytechnic Types of research used in this study using explanatory research methods. The population in this study were all functional Lecturer in Polytechnic Seamanship (PIP) Semarang with the number 71. The sampling technique used in this study is the census. Samples taken by 71 people. Analysis tool used is multiple linear regression. Based on this study concluded: there is a positive and significant impact on the performance of lecturers between competence. There is a positive and significant impact on the performance of lecturers between commitment. There is a positive and significant impact on the performance of the work experience Lecturer. Keywords: competence, commitment, work experience, performance lecturer